OPTIMIZATION OF HYDRAULIC EXCAVATOR WORKING DEVICE (MT) - LI ZhanLong; ZHU XiaoWu; GAO ShanTie; SHI QingLu; CHEN Wei (Jixie qiangdu)
Excavators are the main construction machinery for earth and stone engine. Due to the uncertainties of the work object, load, and operation, the force of the working device of the excavators becomes more complicated. The working device is mainly composed of bucket, arm and boom. Based on different optimization parts, optimization objectives and optimization algorithms, the optimization design of excavators working device has diversity and complexity. An optimization method of working device of hydraulic excavator is introduced in detail, respectively from three aspects of local and overall optimization, new structure application of simulation and modern optimization algorithm. The optimization methods and future development trend of hydraulic excavator working device are summarized, which provides a reference for optimal design of hydraulic excavator working device.